Indian Journal of Marketing : A Bibliometric Analysis - Chaman Sab, M.; Kappi, Mallikarjun; Bagalkoti, Vitthal; Biradar, B. S. (Indian Journal of Marketing, 2020)
This article presented a bibliometric analysis of Indian Journal of Marketing. This journal is a double blind peer reviewed refereed monthly journal, which is being published since 1968. The present data were collected from Scopus database for the time period from 2013-2019. According to our knowledge, there have been no earlier attempts towards its bibliometric characterization. Several different parameters of the journal such as output pattern, authorship pattern, contributing highly prolific authors and organizations were analyzed. Graphs of keyword co-occurrences were also generated to analyze the important themes of research and their trends over the years. We found that the journal output has increased over the years. The authorship trend was found to be towards multi-authored papers. A fair percentage of the publications in the journal are cited. Major change was observed in the themes and trends of content published in Indian Journal of Marketing during the study period, although the journal has remained Indian-focused.